2006
DOI: 10.1079/bjn20051613
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thePhaseolus vulgarisphaseolin level of incorporation, type and thermal treatment on gut characteristics in rats

Abstract: Phaseolus vulgaris phaseolin has been shown to stimulate faecal losses of endogenous N in rats. Experiments with purified phaseolin were carried out in rats to test the hypothesis that these losses reflect intestinal disorders. Phaseolin composition varies depending on its constitutive subunits. Therefore, three phaseolin types (S, T, I) were tested. Phaseolin T was incorporated in varying levels (0, 33, 67 or 100 % of the dietary protein) as raw material in experiment 1. In experiment 2, the three phaseolin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 34 publications
6
39
0
Order By: Relevance
“…This can be related to their low content in sulphur amino acids, the compact proteolysis-resistant structure of the native protein and the presence of antinutritional compounds in the seed, which may affect digestibility of proteins themselves as well as of other components. For example, the nutritive value of common bean phaseolin, the 7S globulin of this species which normally accounts for about 40-50 % of total seed proteins, is limited by a low content in sulphur amino acids and by resistance to enzymatic hydrolysis, even after heat treatment (Montoya et al 2006). The three-dimensional structures of 7S vicilins and 11S legumins have been resolved and confirmed that the two globulins are structurally related (Lawrence et al 1994).…”
Section: Globulinsmentioning
confidence: 98%
“…This can be related to their low content in sulphur amino acids, the compact proteolysis-resistant structure of the native protein and the presence of antinutritional compounds in the seed, which may affect digestibility of proteins themselves as well as of other components. For example, the nutritive value of common bean phaseolin, the 7S globulin of this species which normally accounts for about 40-50 % of total seed proteins, is limited by a low content in sulphur amino acids and by resistance to enzymatic hydrolysis, even after heat treatment (Montoya et al 2006). The three-dimensional structures of 7S vicilins and 11S legumins have been resolved and confirmed that the two globulins are structurally related (Lawrence et al 1994).…”
Section: Globulinsmentioning
confidence: 98%
“…Purification of phaseolin was based on the method described by Montoya et al (2006) with modifications. The flour, prepared as described above, was suspended in 0.5 M NaCl/ 0.025 M HCl, pH 2 (1:20, w/v) for 1 h, and then centrifuged at 13,500g for 30 min.…”
Section: Production Of P Vulgaris Protein Isolatesmentioning
confidence: 99%
“…Common beans (Phaseolus vulgaris L.) contribute up to 57% of recommended dietary protein and 23% of energy to the nutrition of African people [2]. Regular consumption of common bean and other pulses is now promoted by health organizations because it reduces the risk of diseases such as cancer, diabetes or coronary heart diseases [3]. In Tanzania, bean is highly cultivated in the mid to high altitude areas which experience more reliable rainfall and cooler temperature.…”
mentioning
confidence: 99%